TRENDS AND CHALLENGES IN THE DETECTION AND PREVENTION OF HUMAN PAPILLOMAVIRUS. - dos Santos Stopa, Ana Julia; Herdy Alves, Valdecyr; de Holanda Barbosa, Siomara Correia; Gomes Vieira, Bianca Dargam; Pereira Rodrigues, Diego; dos Santos Calandrini, Tatiana do Socorro (Enfermagem Atual in Derme)
Introduction: Human Papillomavirus is a widely spread sexually transmitted infection worldwide, proven to be responsible for a significant number of cervical cancer cases. Objective: This study aims to identify the main trends and challenges in the detection and prevention of the virus, beyond vaccination, through an integrative literature review. Method: This is an integrative literature review, with a systematic search of scientific databases, including studies that address detection methods, prevention strategies, screening programs, and educational interventions in different populations. Results: Although there have been advances in early detection and the implementation of vaccines, there are still significant barriers, such as unequal access to screening programs and a lack of awareness of the issue in vulnerable populations. Conclusion: In addition to vaccination, it is essential to strengthen health education strategies and expand the coverage of screening programs to ensure early detection and reduce the incidence of Human Papillomavirus and its complications.